DEVELOPMENT OF A BANK RISK ASSESSMENT SYSTEM BASED ON DIGITAL TECHNOLOGIES (World Economics and Finance Bulletin, 2026)
This article analyzes the theoretical and practical aspects of developing a risk assessment system in commercial banks based on digital technologies. The study examines the issues of effective management of credit, liquidity, market, and operational risks arising in banking activities. In addition, the impact of modern technologies such as artificial intelligence, big data, blockchain, and digital analytics on the process of bank risk assessment is investigated. During the research process, systematic analysis, comparative analysis, and statistical methods were applied. The results of the analysis show that the introduction of digital technologies into bank risk management systems helps increase the accuracy and speed of risk identification, improve the quality of credit portfolios, and reduce operational errors and fraud cases. As a result of the study, scientifically grounded proposals were developed to improve the risk assessment system in commercial banks.
Keywords: bank risks; commercial banks; risk assessment